2010
DOI: 10.1111/j.1600-0897.2010.00844.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype of NK Cells and Cytotoxic/Apoptotic Mediators Expression in Ectopic Pregnancy

Abstract: Authentic uNK cell population seems to be insufficient to restrict trophoblast invasion because of low expression of cytotoxic/apoptotic mediators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…These cells are also absent in Fallopian tube from ectopic pregnancy (Vassiliadou and Bulmer, 1998; von Rango et al, 2001). However, similar to a recent study (Laskarin et al, 2010), we found substantial numbers of CD3−CD56 dim CD16− NK cells in Fallopian tube from non-pregnant women. Little is known about the function of this NK cell subtype and in the peripheral blood these cells account for less than 1% of all mononuclear cells (Lanier et al, 1986).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These cells are also absent in Fallopian tube from ectopic pregnancy (Vassiliadou and Bulmer, 1998; von Rango et al, 2001). However, similar to a recent study (Laskarin et al, 2010), we found substantial numbers of CD3−CD56 dim CD16− NK cells in Fallopian tube from non-pregnant women. Little is known about the function of this NK cell subtype and in the peripheral blood these cells account for less than 1% of all mononuclear cells (Lanier et al, 1986).…”
Section: Discussionsupporting
confidence: 92%
“…In Fallopian tube from women with ectopic pregnancy, CD3−CD56 bright CD16− NK cells have been shown to be absent from the tubal implantation site (Proll et al, 2000; Vassiliadou and Bulmer, 1998; von Rango et al, 2001). However, a population of CD3−CD56 dim CD16− NK cells has recently been reported in Fallopian tube from women with ectopic pregnancy (Laskarin et al, 2010). The numbers of CD8+ lymphocytes and macrophages have been shown to be elevated at the tubal implantation site compared with elsewhere in the same Fallopian tube (Ulziibat et al, 2006; von Rango et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Isolation of cells from decidual tissue has been described in detail elsewhere (Laskarin et al, 2010). Briefly, decidual tissue was thoroughly rinsed, cut into pieces, and exposed to enzymatic digestion using 0.1% collagenase IV (Sigma, Munich, Germany).…”
Section: Isolation Of Decidual Cells and Peripheral Blood Lymphocytesmentioning
confidence: 99%
“…These cells are heavily endowed with the mediators of cytolytic potential like granulysin (GNLY) and perforin (Veljkovic Vujaklija et al, 2011). Their peripheral blood NK counterparts have a different phenotype (CD56 dim CD16 + ) (Laskarin et al, 2010). More than 85% of the uterine CD56 + NK cells express the GNLY molecule, as well as more than 90% of peripheral blood CD56 + NK cells (Veljkovic Vujaklija et al, 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Our recent results show that first trimester pregnancy decidual tissue is diffusely infiltrated by granulysin-positive cells which accumulate around uterine glands and blood vessels [64, 65]. Granulysin protein was also found in peripheral blood lymphocytes of pregnant women but in significantly lower amounts [64].…”
Section: Granulysin At the Maternal-foetal Interface: A Double-edgmentioning
confidence: 99%